Coeliac disease, autoimmune thyroid disease and primary biliary cirrhosis: Case report - Erkan PARLAK,; Perihan OĞUZ,; Nurgül ŞAŞMAZ,; Tülin ŞAHİN,; Yasemin KOŞAR,; Erdoğan KOVALI, (Turkish Journal of Gastroenterology, 2019)
-